PENGEMBANGAN SISTEM PAKAR PEMILIHAN JAMU DENGAN DIAGNOSA PENYAKIT PADA MANUSIA DENGAN METODE FORWARD CHAINING - Teguh Pradana; Moch. Zul Ilmi; Teguh Arifianto (JURNAL ILMIAH INFORMATIKA, 2021)
Herbal medicine is a medicine from natural ingredients whose properties have not been scientifically proven, in other words, it has not been subjected to clinical or clinical trials, but its properties are trusted by people based on experience. And at this time many herbal products are marketed in general, and not a few people are confused to choose the right herbal medicine according to their circumstances, so people have to consult or ask before choosing, and make the store experience a long queue on customers. Therefore an expert system is needed for herbal medicine so that people can choose the right herbal medicine according to their circumstances or conditions, and this system can reduce the queue at the herbal medicine shop customers. Expert system built in this study uses the forward chaining method. Case study for the system that is "Pasuruan herbal shop fan" which contained 70 types of herbal medicine, the results of tests conducted by this system are in accordance with the diagnosis.